Small innovators: No risk, No return - Stoffman, Noah; Woeppel, Michael; Yavuz, M. Deniz (Journal of Accounting and Economics, 2022)
We show that small innovators (i.e., small firms with recent patent grants) earn higher future returns than small non-innovators. However, we find no such innovation premium among large firms. The higher returns are driven by risk, not underreaction to announcements of recent patent grants. We find that being small and innovative interacts with financial constraints to explain the higher returns. These interactions are more important in the presence of greater information asymmetry. The higher cost of equity among small innovators has implications for their investment, growth, and capital structure decisions.